Unraveling the Link between Financial Performance and Mudaraba Deposit Returns: The Case of Full-fledged Islamic Bank - Kristianingsih Kristianingsih; Mochamad Rizki Ramdani; Hennidah Karnawati; Koernia Purwihartuti; Hazma Hazma; Maya Setiawardani (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The goal of this study was to examine the impact of various factors on the profit-sharing level of Mudaraba deposits held by fully-fledged Islamic banks, including profitability level, profitability level, financing risk level, liquidity level, operational efficiency level, and capital adequacy level. A quantitative descriptive method with panel data regression analysis techniques was used in this investigation. The approaches used for data collecting included documentation and literature study. 168 observational data were collected across 7 Full-Fledged Islamic Banks over the course of six years, from 2017 to 2022. The findings demonstrated that the profit-sharing rate of Mudaraba deposits was significantly influenced by the levels of profitability, financing risk, liquidity, operational efficiency, and capital sufficiency at the same time. The amount of profitability, the level of financing risk, and the level of operational efficiency all somewhat influence the profit-sharing rate for Mudaraba deposits in a positive and significant way. The profit-sharing rate of Mudaraba deposits is unaffected by both liquidity and capital adequacy levels.